Anesthesia protocol for ear surgery in Wistar rats (animal research) - Abhijeet Bhatia; Pranjal Pratim Saikia; Barilin Dkhar; Haphidasara Pyngrope (Animal Models and Experimental Medicine, 2022)
Abstract Objective To formulate an anesthesia protocol for safe and satisfactory anesthesia for ear surgery in rats. Methods The rats were anesthetized with xylazine (10 mg/kg body weight) and ketamine at doses of 80, 50, 40, and 30 mg/kg body weight or with isoflurane anesthesia (2%–3.5% in 100% oxygen; maintenance dose 1.5%–3.5%). The anesthesia induction, surgery, and recovery time were recorded. Results In total, 17 rats were induced by varying doses of ketamine‐xylazine and 28 rats with isoflurane. Mean induction time with ketamine‐xylazine was 6 ± 2.9 min compared with 3.8 ± 1.1 min with isoflurane. Mean recovery time with ketamine‐xylazine was 142.6 ± 49.3 min compared with 4.1 ± 1.2 min with isoflurane. A mortality of 4 animals after developing dyspnea was recorded with ketamine‐xylazine. Conclusion Isoflurane anesthesia offers appropriate induction and recovery times and low mortality rates for the surgeries performed. Isoflurane anesthesia offers reliable results for ear surgery in rats. However, more equipment and technical skills are needed.